Islamic-Based Counseling for Fostering Self Efficacy in Muslim Communities - Faizal, Faizal; Makmun, Fariza; Pratiwi, Tiara Iskandar; Mawarni, Anisa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
The global Muslim community faces challenges in achieving well-being goals. Self-efficacy is key to encouraging active participation and empowerment, but studies examining the effectiveness of Islamic counseling in improving self-efficacy are limited. This study aims to examine the effectiveness of an Islamic counseling intervention in improving self-efficacy in the Muslim community. Using a quantitative approach with a two-group pretest-posttest design, 130 participants aged 18-45 years were divided into experimental and control groups. The intervention consisted of four group sessions, which integrate Islamic values such as tawakal and ikhtiar, reflection on Qur'anic verses, as well as modern psychological techniques such as cognitive restructuring and directed imagination. The three dimensions of self-efficacy based on Bandura's theory—level, generality, and strength—were measured using a validated questionnaire. Two-Way ANOVA analysis showed that the experimental group significantly improved on all three dimensions compared to the control group (p < 0.001), while the effects of age and age versus group interaction were not significant. Post-hoc results strengthened the differences between subgroups. The findings support the effectiveness of Islamic counseling as a values-based approach capable of strengthening self-efficacy across ages and backgrounds. This study makes a theoretical contribution by integrating Islamic spirituality into Bandura's self-efficacy framework, while offering a practical intervention model that can be applied in the mental strengthening of Muslim communities. This research shows that Islamic counseling has potential as an evidence-based approach that is relevant, contextual, and adaptive to the psychological needs of the ummah in the modern era.